2012
DOI: 10.1080/00071668.2012.658025
|View full text |Cite
|
Sign up to set email alerts
|

Gas composition in controlled atmosphere stunning affects turkey meat quality traits

Abstract: 1. Investigations were made into the breast and leg muscle energy metabolism, and the quality of breast meat of turkeys after controlled atmosphere stunning or stun-killing (CAS) with various gas mixtures. In addition, the effect on meat quality of an increase in the chilling rate of turkey breast meat after hypercapnic or anoxic stun-killing was studied. 2. A total of 35 turkey toms within two replicate pens were individually stunned during consecutive weeks using one of 4 CAS methods. The stunning gases te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…However, too rapid chilling should also be avoided. Ylä-Ajos et al (2012) showed that very rapid chilling (0°C) had an adverse effect on turkey breast In row, values (mean ± SD, n= 6 per group) with different superscript (a, b) differ significantly (p b 0.05). meat tenderness and cooking loss in muscles from turkeys stun-killed with carbon dioxide.…”
Section: Meat Qualitymentioning
confidence: 96%
“…However, too rapid chilling should also be avoided. Ylä-Ajos et al (2012) showed that very rapid chilling (0°C) had an adverse effect on turkey breast In row, values (mean ± SD, n= 6 per group) with different superscript (a, b) differ significantly (p b 0.05). meat tenderness and cooking loss in muscles from turkeys stun-killed with carbon dioxide.…”
Section: Meat Qualitymentioning
confidence: 96%